IMPLEMENTATION OF THE MAMDANI METHOD TO DIAGNOSE EXPERT SYSTEM-BASED DISEASES OF THE MOUTH - R. Mahdalena Simanjorang; Agustina Simangunsong (Sean Institute, 2022)
Development of systems and information technology including expert systems that use facts, techniques and knowledge and reasoning in solving problems. Expert systems that are currently developing are systems that adopt the knowledge of an expert in a particular field. In everyday life we ​​often encounter problems faced by humans, including disease problems that exist in the human body, so we need to consult an expert in the health sector to solve these problems. However, sometimes patients with disease cannot consult an expert due to the large number of patients as well as time and cost issues. In these existing problems, it is necessary to develop a system that can help these patients, namely by developing an expert system model for diagnosing oral disease by utilizing the Mamdani method. The mamdani method will assist in diagnosing the disease.